Reframing Freelancer Retention: The Role of Hybrid Work Culture in Shariah Sustainable Workforce Management on Digital Platforms - Muhardi; Sulaiman; B, Mustamin (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose – This study investigates the influence of hybrid work culture, work-life balance, organizational support, and employee engagement on freelancer retention within the Upwork platform. Method – Using a quantitative approach with 210 respondents, data were analyzed through Structural Equation Modeling to explore relational dynamics among the key variables. Findings – Results indicate that hybrid work culture significantly enhances retention, particularly when mediated by strong organizational support and high levels of engagement. Work-life balance plays a moderating role, reinforcing the positive effects of flexible work models on freelancers’ long-term commitment. Practical implications – Theoretically, this study extends retention discourse into the gig economy, bridging management and labor sustainability frameworks. From a Shariah perspective, the findings emphasize equitable treatment, well-being, and dignity in employment practices, aligning with the objectives of maqāṣid al-sharī‘ah. Originality/value digital platforms and Islamic financial institutions seeking to design sustainable, ethical, and resilient workforce strategies